Bahasa Indonesia Bahasa Inggris - Elshadai Gracia Carolina Rampengan Rampengan; Semmy Wellem Taju; Venisa Tewu (CogITo Smart Journal, 2023)
Klabat University provides residential facilities for students, better known as a dormitory. Information services regarding dormitories and reservation rooms at Klabat University are still managed manually between the dormitory and students. Some problems occur when students want to find information and/or reserve a room at the same time. From the problems that have been observed, researchers have designed a Chatbot to facilitate the students to find for information as well as reserve dormitory rooms. The development method used in this research is the prototyping model. To design a chatbot by implementing two-way communication, researchers implemented Natural Language Processing technique with a Machine Learning approach. The result of this research is a new Chatbot widget as a virtual assistant for information services and reservation rooms in the dormitory at Klabat University